Ice nucleation behaviour on sol–gel coatings with different surface energy and roughness - Fu, Qi Tao (2016)
In this paper, the ice nucleation temperatures of 10 μL water droplets on a series of sol–gel coatings with different roughness and surface energies were obtained using a customized automatic measurement system. Classical nucleation theory was then employed to explain the different icing behaviour on the coatings. It was found that the wetting mode at low temperatures is strongly correlated with the icing behavior of the droplets on the surfaces. Ice-phobic coatings can lower the icing temperature of the droplet on the surface by up to 6.9 °C compared with non-icephobic ones. Using classical nucleation theory, our results support some recent observations that the dominant nucleation sites are along the substrate–water–vapour three-phase contact line rather than at the substrate–water interface.